Greek Debt Crisis: The "@-euro" a New Possible Solution to Greek Debt Crisis - Panagiotis Mantalos (Örebro University School of Business, 2015)
We introducing the new idea, of "@-euro" is a self-part-financiering monetary policy. This new idea, introduced more money (liquidity) to Greek state, and a system to collect taxes from the black economy. This idea, which is a possible solution to the Greek Crisis applied in a 7-years alternative Budget. The "@-euro" has two characteristics, first self-financiering and self-discipline. The produced New MTFS with exceptional positive results, with 43,00 billion surplus after that we have pay 113,00 billion Euro back to the creditors in a 7 year period. Moreover, no negative effects of austerity. There is fiscal stimulus without inflation!
Keywords: C22; E62; F33; H63; O40; 330; Austerity; Government Budget; "@-euro"